Penguatan Pendidikan Karakter di Sekolah Dasar Islam melalui Pendekatan Pembelajaran Holistik - Galih Orlando; Syanty Ericka; Henrawansyah Harahap; Yuslinda; Ali Sadikin Ritonga (Insan Zenius Ilmiah, 2025)
This study aims to analyze the effectiveness of a holistic learning approach in strengthening character education in Islamic elementary schools. Education at this level is not only aimed at mastering academic knowledge, but also instilling moral, spiritual, and social values ​​​​in accordance with Islamic teachings. The reality in the field shows that learning practices are still dominated by conventional methods that emphasize memorization, while character building is often positioned as an additional aspect. This creates a gap between the ideal goals of Islamic education and the implementation of daily learning. This study used a literature study method by analyzing various literature in the form of books, scientific articles, and relevant curriculum documents. A descriptive qualitative approach was used to identify key concepts, compare expert views, and compile a synthesis regarding holistic learning and its relevance to character education in Islamic elementary schools. The results show that a holistic approach is able to strengthen character education by integrating cognitive, affective, psychomotor, and spiritual aspects in the learning process. Strategies that can be implemented include integrative thematic learning, Project Based Learning, teacher role models, religious habits, and the development of an Islamic school culture. However, challenges faced include limited teacher competence, limited learning facilities, and an educational orientation that emphasizes academic achievement